Does female entrepreneurship add in economic growth? Evidence from twenty-five countries - Salim MORCHED; Anis JARBOUI (Academic Finance, 2018)
Recent researches in the field of entrepreneurship give a renewed interest in the role of women entrepreneurship in the economic development. This document aims to draw up an analysis of the effect of female entrepreneurship on economic growth using a panel data over the period 2000-2014 for a sample of twenty-five (developed and developing) countries. Results show that female entrepreneurship has a significant negative effect but also entrepreneurship is considered the channel, it has an indirect impact on economic growth even business creation has been a real engine of economic development; these are seen as a means to generate employment opportunities, income distribution, wealth creation and poverty reduction. Some recommendations are presented, in order to support of government initiatives and the effect on women-owned business performance which are also important.